An isocaloric glucose-fructose beverage`s effect on simulated 100-km cycling performance compared with a glucose-only beverage - Triplett, D.; Doyle, J. A.; Rupp, J. C.; Benardot, D. (International Journal of Sport Nutrition and Exercise Metabolism, 2010)
A number of recent research studies have demonstrated that providing glucose and fructose together in a beverage consumed during exercise results in significantly higher oxidation rates of exogenous carbohydrate (CHO) than consuming glucose alone. However, there is insufficient evidence to determine whether the increased exogenous CHO oxidation improves endurance performance. The purpose of this study was to determine whether consuming a beverage containing glucose and fructose (GF) would result in improved cycling performance compared with an isocaloric glucose-only beverage (G). Nine male competitive cyclists (32.6 ± 5.8 yr, peak oxygen uptake 61.5 ± 7.9 ml · kg-1 · min-1) completed a familiarization trial and then 2 simulated 100-km cycling time trials on an electronically braked Lode cycle ergometer separated by 5-7 d. During the randomly ordered experimental trials, participants received 36 g of CHO of either G or GF in 250 ml of water every 15 min. All 9 participants completed the 100-km time trial significantly faster when they received the GF beverage than with G (204.0 ± 23.7 vs. 220.6 ± 36.6 min; p = .023). There was no difference at any time point between trials for blood glucose or for blood lactate. Total CHO oxidation increased significantly from rest during exercise but was not statistically significant between the GF and G trials, although there was a trend for CHO oxidation to be higher with GF in the latter stages of the time trial. Consumption of a CHO beverage containing glucose and fructose results in improved 100-km cycling performance compared with an isocaloric glucose-only beverage.